2021
DOI: 10.3390/nu13114150
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients and Dietary Approaches in Patients with Type 2 Diabetes Mellitus and Cardiovascular Disease: A Narrative Review

Abstract: Cardiovascular disease (CVD) is the most common cause of morbidity and mortality in developed countries. The prevalence of CVD is much higher in patients with type 2 diabetes mellitus (T2DM), who may benefit from lifestyle changes, which include adapted diets. In this review, we provide the role of different groups of nutrients in patients with T2DM and CVD, as well as dietary approaches that have been associated with better and worse outcomes in those patients. Many different diets and supplements have proved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 225 publications
(241 reference statements)
0
6
0
Order By: Relevance
“…Overt proteinuria: During this stage, the renal function is compromised, resulting in the kidneys being unable to retain proteins effectively. Consequently, there is a notable increase in protein excretion in the urine [ 20 ].…”
Section: Reviewmentioning
confidence: 99%
“…Overt proteinuria: During this stage, the renal function is compromised, resulting in the kidneys being unable to retain proteins effectively. Consequently, there is a notable increase in protein excretion in the urine [ 20 ].…”
Section: Reviewmentioning
confidence: 99%
“…In addition to the proper amount of fish in the diet, our results indicate that red meat and fast food products are (although infrequently) present in the diet of patients. Many studies have shown that the limited intake of saturated fats, also present in red meat, contributed to a reduced cardiovascular risk [ 25 , 26 , 27 ]. The products mentioned above and fast foods are also natural sources of sodium.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of nutrition in preventing CVDs and T2DM individually is well established in several studies that focused on macronutrients (carbohydrates, fats, proteins, macrominerals), micronutrients (vitamins and other minerals), and other nutrients (fiber, and dietary supplements) to control the balance between energy expenditure and calorie intake. It is necessary to highlight the importance of food quality over food quantity by having dietary patterns rich in whole grains, fruit, vegetables, nuts, legumes, fish, or vegetable oils and poor in processed meats, refined grains, refined carbohydrates, and salt [18][19][20][21]. An energy-dense dieatry pattern high in saturated fat and free sugar causes the temporary emergence of some metabolic and physiological derangements or dysfunctions, including oxidative stress, low-grade inflammation, and endothelial dysfunction, which act directly on postprandial plasma triglycerides and glucose.…”
Section: Nutrition-related Cardiometabolic Risk Factorsmentioning
confidence: 99%